E-scooters: competition with shared bicycles and relationship to public transport. Issue 3 (2nd September 2021) - Nawaro, Łukasz
ABSTRACT: E-scooters have recently emerged as an alternative means of transportation in cities. It remains unclear whether e-scooters compete for users with bicycles – another mode of shared micromobility. Their relationship to public transport can be complementary or substitutionary, and it has not been ascertained which effect prevails. This paper contributes to answering these questions using empirical trip-level data on Warsaw. We find that there is little difference between e-scooters' and bicycles' speed and that placement of bicycle docks influences number of e-scooter trips, which is an indication that they compete for the same market. E-scooters' trip data shows that they are more complementary to rapid public transport and may contribute to solving the last-mile problem. We discuss the importance of results for optimal policy promoting environmentally friendly transportation and identify further research directions.